Selective Inhibition of 2-Oxoglutarate and 2-Oxoadipate Dehydrogenases by the Phosphonate Analogs of Their 2-Oxo Acid Substrates - Artiukhov, Artem V.; Kazantsev, Alexey V.; Lukashev, Nikolay V.; Bellinzoni, Marco; Bunik, Victoria I. (Frontiers in Chemistry, 2021)
Phosphonate analogues of pyruvate and 2-oxoglutarate are established specific inhibitors of cognate 2-oxo acid dehydrogenases. The present work develops application of this class of compounds to specific in vivo inhibition of 2-oxoglutarate dehydrogenase (OGDH) and its isoenzyme, 2-oxoadipate dehydrogenase (OADH). The isoenzymes-enriched preparations from the rat tissues with different expression of OADH and OGDH are used to characterize their interaction with 2-oxoglutarate (OG), 2-oxoadipate (OA) and the phosphonate analogues. Despite a 100-fold difference in the isoenzymes ratio in the heart and liver, similar Michaelis saturations by OG are inherent in the enzyme preparations from these tissues (KmOG = 0.45±0.06 and 0.27±0.026 mM, respectively), indicating no significant contribution of OADH to the OGDH reaction, or similar affinities of the isoenzymes to OG. However, the preparations differ in the catalysis of OADH reaction. The heart preparation, where OADH/OGDH ratio is ≈ 0.01, possesses low-affinity sites to OA (KmOA = 0.55±0.07 mM). The liver preparation, where OADH/OGDH ratio is ≈ 1.6, demonstrates a biphasic saturation with OA: The low-affinity sites (Km,2OA = 0.45±0.12 mM) are similar to those of the heart preparation; the high-affinity sites (Km,1OA = 0.008±0.001 mM), revealed in the liver preparation only, are attributed to OADH. Phosphonate analogues of C5-C7 dicarboxylic 2-oxo acids inhibit OGDH and OADH competitively to 2-oxo substrates in all sites. The high-affinity sites for OA are affected the least by the C5 analogue (succinyl phosphonate) and the most by the C7 one (adipoyl phosphonate). The opposite reactivity is inherent in both the low-affinity OA-binding sites and OG-binding sites. The C6 analogue (glutaryl phosphonate) does not exhibit a significant preference to either OADH or OGDH. Structural analysis of the phosphonates binding to OADH and OGDH reveals the substitution of a tyrosine residue in OGDH for the serine residue in OADH among structural determinants of the preferential binding of the bulkier ligands to OADH. The consistent kinetic and structural results expose adipoyl phosphonate as a valuable pharmacological tool for specific in vivo inhibition of the DHTKD1-encoded OADH, a new member of mammalian family of 2-oxo acid dehydrogenases, up-regulated in some cancers and associated with diabetes and obesity.